Praktik Komunikasi Persuasif Ustadz Dalam Menumbuhkan Disiplin Santri di Pondok Tahfidz Nurul Qur’an Bekasi - Syafruddin, Syafruddin; Hamid, Abdul; Anim, Sarbini (Institut Agama Islam Negeri Kendari, 2026)
This study examines the persuasive communication practices employed by ustadz in fostering students’ discipline at Pondok Tahfidz Nurul Qur’an Bekasi. The study aims to analyze the forms of persuasive communication used by ustadz, the process of disciplinary development through persuasive communication, students’ responses to such communication, and the supporting and inhibiting factors affecting its implementation. This research employed a qualitative ethnographic approach. Data were collected through participant observation, in-depth interviews, and documentation involving the pesantren leader, Tahfidz teachers, teachers of kitab kuning, senior students, and junior students. Data were analyzed through data organization, categorization, interpretation, and identification of cultural themes, while source and method triangulation were used to ensure the credibility of the findings. The results reveal that persuasive communication is implemented through advice and guidance, role modeling, habituation, supervision, and personal approaches. The process of fostering discipline occurs through the internalization of values, daily habituation, continuous supervision, and ongoing evaluation. Students generally respond positively to persuasive communication, as reflected in their acceptance of guidance, appreciation of teachers’ role modeling, and improvements in disciplinary behavior. The effectiveness of persuasive communication is supported by the credibility of the ustadz, intensive interactions between teachers and students, and a conducive pesantren culture. However, differences in students’ backgrounds and personalities, adaptation challenges, and fluctuating motivation constitute obstacles to the communication process. These findings demonstrate that persuasive communication plays a significant role in cultivating discipline among students within the cultural and educational environment of the pesantren.